(untitled) (Olhar de Professor, 2021)
This paper presents an overview of videos that were broadcasted on YouTuve in 2020 on the following subject: early childhood education in pandemic times. Using netnography as methodology, we researched videos that were broadcasted between February 10th and June 12th, and we found 78 broadcasts, which were divided into two categories in order to improve the analysis: (i) live broadcasts that bring indications of defense / dissemination (directly or indirectly) of private ideas and concepts about childhood; and (ii) live broadcasts focused in the analysis of the current conjecture, discussing early childhood education in the pandemic context from a critical, non-partisan perspective and with the main premise of defending children and their childhoods in this context. By systematizing actions from the virtual universe to the written register, we seek to ensure that they resist time, preventing from the risk of dissolving into the logic of the “digital speed”, giving materiality to these analyzes that were done in real time, composing a collection capable of giving visibility to the gaps that exist concerning the assistance for the early childhood in the pandemic period.